Perceived privacy risk in the Internet of Things: determinants, consequences, and contingencies in the case of connected cars - Nils Koester; Patrick Cichy; David Antons; Torsten Oliver Salge (Electronic Markets, 2022)
The Internet of Things (IoT) is permeating all areas of life. However, connected devices are associated with substantial risks to users' privacy, as they rely on the collection and exploitation of personal data. The case of connected cars demonstrates that these risks may be more profound in the IoT than in extant contexts, as both a user's informational and physical space are intruded. We leverage this unique setting to collect rich context-immersive interview (n = 33) and large-scale survey data (n = 791). Our work extends prior theory by providing a better understanding of the formation of users' privacy risk perceptions, the effect such perceptions have on users' willingness to share data, and how these relationships in turn are affected by inter-individual differences in individuals' regulatory focus, thinking style, and institutional trust.
Keywords: O33; 620; Information privacy; Disclosure decision-making; Perceived privacy risk; Connected cars; Internet of Things